Age differences in high frequency phasic heart rate variability and performance response to increased executive function load in three executive function tasks - Byrd, Dana L.; Reuther, Erin T.; McNamara, Joseph P. H.; DeLucca, Teri L.; Berg, William K. (Frontiers in Psychology, 2015)
The current study examines similarity or disparity of a frontally-mediated physiological response of mental effort among multiple executive functioning tasks between children and adults. Task performance and phasic heart rate variability (HRV) were recorded in children (6 to 10 years old) and adults in an examination of age differences in executive functioning skills during periods of increased demand. Executive load levels were varied by increasing the difficulty levels of three executive functioning tasks: inhibition (IN), working memory (WM), and planning/problem solving (PL). Behavioral performance decreased in all tasks with increased executive demand in both children and adults. Adults’ phasic high frequency HRV was suppressed during the management of increased IN and WM load. Children’s phasic HRV was suppressed during the management of moderate WM load. HRV was not suppressed during either children’s or adults’ increasing load during the PL task. High frequency phasic HRV may be most sensitive to executive function tasks that have a time-response pressure, and simply requiring performance on a self-paced task requiring frontal lobe activation may not be enough to generate HRV responsivity to increasing demand.